Metroxylon sagu rottb. fruit flour as potential prebiotics for selected probiotics and phytochemical profiling of its methanolic extract by LC-MS/MS - Fadhilla, Reza; Yuliana, Nancy Dewi; Kusnandar, Feri; Kusumaningrum, Harsi Dewantari (Penerbit Universiti Kebangsaan Malaysia, 2024)
The plant of Metroxylon sago Rottb. which is found abundantly in Indonesia, Malaysia, Philippines, and Papua New Guinea, is famous as carbohydrate producing plants. The sago fruit has not been yet extensively used, although they are rich in oligosaccharides which is potential as prebiotic. Sago fruit flour was studied as growth substrate for five selected probiotics and phytochemical profile of its methanol extracts were determined. All bacteria grew well up to 24 h on the growth medium containing sago fruit flour as carbohydrate substitute. However, Lacticaseibacillus rhamnosus FNCC 0099 and Lactobacillus acidophilus FNCC 0051 showed viability stability up to 72 h, while the others were slightly decreased. The sago fruit flour contained 20.4 mg/g total sugars, 14.8 mg QE/g flavonoids, and 36.7 mg GAE/g phenolics. After extraction of the fruit flour with 80% methanol using an ultrasonicator at 55 °C at 40 kHz for 40 min, the extract was analysed for its phytochemical profiles using untargeted LC-MS/MS screening with negative ionization mode. Seven compounds categorised in three distinct groups i.e., sugar alcohol, plant glycosides and fatty acids, have been identified as having possible prebiotic activity. These include ((1xi)-1,5-anhydro-2,3,6-tris-O-(carboxymethyl)-1-methyl-4-Omethyl-D-glucitol), quercitrin, (15Z)-9,12,13-trihydroxy-15-octadecenoic acid, corchorifatty acid F, 3,5-dihydroxy-2- (4-hydroxyphenyl)-4-oxo-3,4-dihydro-2H-chromen-7-yl-hexopyranoside, gynocardin, and (4-methylumbelliferone)-βD-glucopyranoside. As the sago fruit flour has been proved as potential prebiotic in this study, its extensive prebiotics activity, prebiotic index, and stability under digestive condition will be subjected for further study.